Grounded Series/Parallel RL/RC Immittance Simulations with a Single VDTA - Pukkalanun, Tattaya; Moonmuang, Pitchayanin; Tangsrirat, Worapong (My University, 2022)
This paper discusses actively simulated RL and RC immittance simulator circuits. Only one voltage difference transconductance amplifier (VDTA) and one grounded capacitor are required for each realized simulator. The proposed simulator concept can realize all the possible series and parallel RL/RC impedance functions, with the simulated equivalent elements being tunable both electronically and separately through the VDTA's transconductance gains. The impacts of VDTA non-idealities on realized simulator performance are examined. The numerical simulations using PSPICE program, as well as experimental measurements utilizing commercially available IC CA3080s, are provided to prove the practicability of the circuits.
Keywords: electronically adjustable; impedance simulator; Voltage Difference Transconductance Amplifier (VDTA)